BSTP Review of 12 Case Studies Discussing the Challenges, Pathology, Immunogenicity, and Mechanisms of Inhaled Biologics. (February 2021) - Hall, A. Peter; Tepper, Jeffrey S.; Boyle, Molly H.; Cary, Maurice G.; Flandre, Thierry G.; Piaia, Alessandro; Tarnow, Inge; Macri, Nicholas P.; Freke, Mark C.; Nikula, Kristen J.; Paul, Graham R.; Cauvin, Annick; et al.
The inhalation route is a relatively novel drug delivery route for biotherapeutics and, as a result, there is a paucity of published data and experience within the toxicology/pathology community. In recent years, findings arising in toxicology studies with inhaled biologics have provoked concern and regulatory challenges due, in part, to the lack of understanding of the expected pathology, mechanisms, and adversity induced by this mode of delivery. In this manuscript, the authors describe 12 case studies, comprising 18 toxicology studies, using a range of inhaled biotherapeutics (monoclonal antibodies, fragment antigen-binding antibodies, domain antibodies, therapeutic proteins/peptides, and an oligonucleotide) in rodents, nonhuman primates (NHPs), and the rabbit in subacute (1 week) to chronic (26 weeks) toxicology studies. Analysis of the data revealed that many of these molecules were associated with a characteristic pattern of toxicity with high levels of immunogenicity. Microscopic changes in the airways consisted of a predominantly lymphoid perivascular/peribronchiolar (PV/PB) mononuclear inflammatory cell (MIC) infiltrate, whereas changes in the terminal airways/alveoli were characterized by simple ("uncomplicated") increases in macrophages or inflammatory cell infiltrates ranging from mixed inflammatory cell infiltration to inflammation. The PV/PB MIC changes were considered most likely secondary to immunogenicity, whereas simple increases in alveolar macrophages were most likely secondary to clearance mechanisms. Alveolar inflammatory cell infiltrates and inflammation were likely induced by immune modulation or stimulation through pharmacologic effects on target biology or type III hypersensitivity (immune complex disease). Finally, a group of experts provide introductory thoughts regarding the adversity of inhaled biotherapeutics and the basis for reasonable differences of opinion that might arise between toxicologists, pathologists, and regulators.